Undergraduate Students’ Perceptions on Online English Proficiency Test - Nurmala Hendrawaty; Tri Angkarini; Ayu Bandu Retnomurti (Universitas Pendidikan Ganesha, 2023)
Along with the development of educational technology, the online Computer-Based Test (CBT) application is one of the innovations in taking an online test. This study intended to analyze undergraduate students’ perceptions of online EPT. The samples were taken with purposive sampling, and they were 68 participants from English Education Program. The research instrument was an online questionnaire with sixteen closed-ended questions using a Likert scale of four items and two open-ended questions. The data analysis employed a qualitative descriptive method to analyze six topics: perspectives on online EPT implementation, online EPT preparation, attitude during the online EPT, point of view on e-application, the expectation of test results, and difficulty level of online EPT. The findings revealed that most undergraduate students positively perceived the online EPT. Apart from the technical issues, e-ujian.com is a practical online test application. This research implies that institutions should consider these issues to enhance the quality of e-ujian.com as an online EPT implementation in the following semesters.